Contrast media-induced nephropathy: how has Italy contributed in the past 30 years? A systematic review - Sessa M; Rossi C; Mascolo A; Scavone C; di Mauro G; Grassi R; Sportiello L; Cappabianca S; Rafaniello C (Dove Medical Press, 2017)
Maurizio Sessa,1,* Claudia Rossi,2,* Annamaria Mascolo,1 Cristina Scavone,1 Gabriella di Mauro,1 Roberto Grassi,2 Liberata Sportiello,1 Salvatore Cappabianca,2 Concetta Rafaniello1 1Section of Pharmacology “L Donatelli”, Department of Experimental Medicine, University of Campania “L Vanvitelli”, Naples, Italy; 2Section of Radiology and Radiotherapy, Department of Clinical and Experimental Medicine “Magrassi-Lanzara”, University of Campania “L Vanvitelli”, Naples, Italy *These authors contributed equally to this work Background and objective: The use of contrast media in Italy has exponentially increased in the past 3 decades. However, it is unknown whether there has been an increase in clinical research evaluating the risks associated with contrast media usage, especially regarding contrast-induced nephropathy. To fill this gap in knowledge, we performed a systematic review.Study eligibility criteria: Meta-analyses, observational studies, and clinical trials assessing contrast media-induced nephropathy as the safety outcome, in which at least one author was affiliated with an Italian university/health care structure, were eligble.Data sources: Ovid MEDLINE, Ovid Embase, Cochrane Methodology Register, and Web of Science were screened.Participants: Men and women exposed to contrast media.Results: In total, 60 original articles were retrieved with an incremental trend between 1990 and 2017. Cohort studies were the most common study design represented. In total, 45 of 60 (75.0%) studies were monocenter studies and 41 of 60 (68.3%) received no funding. In all, 91.7% of studies disclosed no conflicts of interest and 81.7% had no external collaboration. Most of the studies provided a level of evidence of III-2 (32/60; 53.3%) and II (23/60; 38.3%). In total, 50 of 60 studies (83.3%) were published in a scientific journal ranked in the first quartile of their subject area.Conclusion: There was an increased number of studies evaluating contrast-induced nephropathy in Italy during the last three decades. These studies covered procedures to prevent contrast-induced nephropathy or aimed to identify risk factors, biomarkers, and scores, and their related prognosis. Keywords: nephropathy, contrast media, Italy, systematic review, drug safety, adverse drug reaction, pharmacovigilance, post-marketing surveillance